Hemostasis and thrombosis in obstetrics & gynecology - Paidas, Michael J; Hossain, Nazli; Shamsi, Tahir S; Rodger, Marc A; Langhoff-Roos, Jens; Lockwood, Charles J (WILEY, 2011)
Reproductive hemostasis: A global approach to a global challenge A hemostatic change in women through their reproductive lifetime is emerging as an issue of global importance. No wonder, as obstetric hemorrhage remains a major cause of maternal mortality in both developed and developing countries. Thrombophilias and pulmonary embolisms are a threat to maternal and fetal well-being. Hemostasis and Thrombosis in Obstetrics & Gynecology provides a framework for assessing and managing hemostatic disorders in women. Written by an international team, it provides globally applicable guidelines for obstetric hematology. The practical approach to clinical management includes: * Hematologic changes in pregnancy * Red cell disorders * Platelet disorders * Inherited and acquired thrombophilia * Inherited bleeding disorders * Postpartum hemorrhage Blood and bleeding disorders in women can be managed by obstetrician-gynecologists or hematologists, separately or together. Hemostasis and Thrombosis in Obstetrics & Gynecology provides specialists from both disciplines with the information necessary to manage their patients effectively.